2009
DOI: 10.1007/s10552-009-9322-2
|View full text |Cite
|
Sign up to set email alerts
|

Race in ovarian cancer treatment and survival: a systematic review with meta-analysis

Abstract: These results suggest that racial disparities in ovarian cancer are not due to underlying biological differences rather to the unequal application of existing treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…Most previous studies in this area focused on disparities by ethnicity or marital status, lacked socioeconomic information at the individual level and had limited data on prognostic factors [3,10,11,[14][15][16][17]. We used nationwide clinical and administrative registers to retrieve data on important prognostic factors and individual socioeconomic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in this area focused on disparities by ethnicity or marital status, lacked socioeconomic information at the individual level and had limited data on prognostic factors [3,10,11,[14][15][16][17]. We used nationwide clinical and administrative registers to retrieve data on important prognostic factors and individual socioeconomic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al and Redaniel et al reported that the difference in access to health care would have a more important influence on the survival of ovarian cancer than differences in demographic genetics [33,34]. The 5-year survival of ovarian cancer patients did not show a significant difference per ethnicity in the meta-analysis performed by Terplan et al [35]. Accordingly, it appears as though there is no big problem in applying the meta-analysis results from Western patient to Koreans.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated a treatment disparity among Black women diagnosed with ovarian cancer (8,15,(19)(20)(21). A comprehensive literature review published in 2013 highlighted that Black women suffer discrepancies in care from diagnosis to treatment that detrimentally affects survival for all stages of disease (7).…”
Section: Discussionmentioning
confidence: 99%
“…Each hospital discharge abstract in the Patient Discharge Database contains demographic data (e.g. gender, age, race/ethnicity, type of insurance, zip code of residence), reason for admission, primary and secondary (up to 24) diagnoses, primary and secondary (up to 20) procedures, dates of procedure, and discharge information (e.g. length of stay, disposition).…”
Section: Methodsmentioning
confidence: 99%